2022
DOI: 10.3389/fsurg.2022.939223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative dexmedetomidine on hepatic ischemia-reperfusion injury in pediatric living-related liver transplantation: A propensity score matching analysis

Abstract: BackgroundHepatic ischemia-reperfusion injury (HIRI) is largely unavoidable during liver transplantation (LT). Dexmedetomidine (DEX), an α2-adrenergic agonist, exerts a variety of organ-protective effects in pediatric populations. However, evidence remains relatively limited about its hepatoprotective effects in pediatric living-related LT.MethodsA total of 121 pediatric patients undergoing living-related LT from June 2015 to December 2018 in our hospital were enrolled. They were classified into DEX or non-DEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%
“…No new clinical trial was found after searching the clinical trial registration platform ClinicalTrial.gov and WHO ICTRP. Finally, nine studies were included in the meta-analysis, with a total of 648 participants ( Choi et al, 2016 ; Fayed et al, 2016 ; Sayed and Yassen, 2016 ; Xu et al, 2016 ; Lee et al, 2020 ; Lee et al, 2021 ; Ustun et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2022 ). See Figure 1 for the combined search results.…”
Section: Resultsmentioning
confidence: 99%